PENDAMPINGAN EDUKASI POLA ASUH EFEKTIF BERBASIS PROGAM PARENTING BAGI ORANG TUA DI KELURAHAN MATALOKO UNTUK MEMBENTUK KARAKTER ANAK - Angelina Kurnia Juita; Andi Nafsia; Prisko Yanuarius Djawaria Pare; Maria Eleonora Lejo (LPPM Institut Pendidikan Nusantara Global, 2025)
This parenting-based educational mentoring program is being implemented as an effort to increase the knowledge, skills, and awareness of parents in Mataloko Village, Golewa District, Ngada Regency in implementing appropriate and effective parenting patterns for their children. The mentoring activities are carried out through the delivery of materials, discussions, and direct practice related to effective parenting patterns for the formation of children's character, emphasizing the importance of positive communication, consistent discipline, and providing role models in the character-building process. Through this program, parents are guided to understand their important role as the first and primary educators in the family, as well as how daily parenting patterns directly impact the development of children's character. The results of the activity indicate that parenting mentoring can improve parents' understanding of effective and appropriate parenting strategies for children. Parents become better able to manage emotions, build closeness with their children, and implement rules that support the formation of positive character traits such as responsibility, independence, and discipline. This program also provides a space for reflection for parents to re-evaluate their parenting practices. Therefore, the educational mentoring activities on effective parenting are expected to be a concrete step in strengthening the quality of parenting in Mataloko Village, Golewa District, Ngada Regency, so as to create a generation of children with good character and ready to face future challenges.